Impression management : an international comparison of financial graphs in annual reports - Chong, Sue Fang (2008)
This study purports to find any possible differences in the incidence of graphic usage as well as the extent of graphic distortions among eight countries' annual reports. Our study also attempts to validate a set of graphical metrics in a real world setting.